Вплив кольорової гами навчальної літератури на сприйняття дитиною шкільного матеріалу - Шипова, М. (My University, 2020)
he system of preschool education and primary school age of children has often changed recently. In the design of children's books, the layout of the text, illustrative material, font size, used headset, various schemes and auxiliary drawings play a very important role. Also plays a significant swarm of colors, in which this or that textbook is made
Keywords: кольорова гама; навчальна література; сприйняття шкільного матеріалу